The Relationship Between Secondary School Students’ English Speaking Anxiety, English Speaking Self-Efficacy And Personality Traits - Nurullah Özcanlı; İshak Kozikoğlu (Educational Academic Research)
This study aims to investigate the relationship between secondary school students' English-speaking anxiety, English-speaking self-efficacy, and personality traits. Conducted as a correlational study, it involved 920 students from secondary schools in the central districts of Van, selected through the cluster sampling method. Data were collected using the "Five-Factor Personality Scale," "English Speaking Self-Efficacy Scale," and "English Speaking Anxiety Scale." The analysis employed Pearson Product-Moment Correlation Coefficient and stepwise regression techniques. The findings revealed significant interrelations among students' personality traits, English-speaking anxiety, and self-efficacy perceptions. Specifically, students' English-speaking self-efficacy and the personality traits of openness to experience, extraversion, neuroticism, and agreeableness collectively accounted for 27.1% of the variance in English-speaking anxiety. Given the critical role of English-speaking anxiety in language acquisition, it is recommended that teachers consider these variables when guiding students. They should create motivating and supportive learning environments that foster self-expression and establish a positive classroom atmosphere conducive to foreign language learning.